First ply failure analysis of laminated composite beam for different boundary conditions under thermo mechanical loading - Choudhury, Arnab; Mondal, Samar Chandra; Sarkar, Susenjit (Zielona Góra: Uniwersytet Zielonogórski)
Failure analysis of a laminated composite beam subjected to uniformly distributed load and thermal load is studied for different boundary conditions and fiber orientation angles, based on first ply failure load. Three different boundary conditions are studied: simply supported, fixed-fixed and fixed-free. The strength ratio is computed and compared for different failure theories.
Keywords: first ply failure load; fiber orientation angle; aspect ratio; hybrid composite beam; strength ratio